2008
DOI: 10.1007/s10792-008-9224-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of raloxifene hydrochloride on ocular hemodynamics and visual function

Abstract: Raloxifene therapy at 60 mg/day had no clinically significant impact on BP, IOP or OBF in post-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(49 reference statements)
0
2
0
Order By: Relevance
“… 172 Three months treatment with the selective estrogen-receptor modulator raloxifene had no effects on ocular blood flow in postmenopausal women. 173 It is, however, possible that raloxifene has an effect on ocular blood flow regulation in response to changes in OPP. Raloxifene lowers vascular tone via upregulation of the production of nitric oxide (NO) as well as through inhibition of L-type calcium channels in vascular smooth muscle cells.…”
Section: The Influence Of Sex Hormones On Ocular Blood Flowmentioning
confidence: 99%
“… 172 Three months treatment with the selective estrogen-receptor modulator raloxifene had no effects on ocular blood flow in postmenopausal women. 173 It is, however, possible that raloxifene has an effect on ocular blood flow regulation in response to changes in OPP. Raloxifene lowers vascular tone via upregulation of the production of nitric oxide (NO) as well as through inhibition of L-type calcium channels in vascular smooth muscle cells.…”
Section: The Influence Of Sex Hormones On Ocular Blood Flowmentioning
confidence: 99%
“…Conversely, another study found no difference in retinal or retrobulbar blow flow measurements in comparing the effects of Raloxifene on postmenopausal women. 54 Retrobulbar blood vessel caliber analysis in several large studies failed to reveal any differences between males and females. [55][56] These findings suggest the importance of sex hormones as viable candidates to explain retrobulbar blood flow differences among men and women.…”
Section: Gendermentioning
confidence: 99%